Oral Administration of Nanopeptide CMCS-20H Conspicuously Boosts Immunity and Precautionary Effect Against Bacterial Infection in Fish - Huo, Xingchen; Wang, Zhensheng; Xiao, Xun; Yang, Chunrong; Su, Jianguo (Frontiers in Immunology, 2022)
Massive mortalities caused by bacterial infections in intensive aquaculture result in serious economic losses. In this study, a novel antimicrobial peptide gcIFN-20H was efficiently expressed in Pichia pastoris (GS115) and loaded on carboxylmethyl chitosan (CMCS) to prepare CMCS-20H nanoparticles. Through physical characterization assays (TEM, DLS, BCA, and Raman) and biological activity tests (Antimicrobial activity and cytotoxicity), CMCS-20H nanopeptide was verified to be spherical nanoparticles with sustained release, antimicrobial activity and negligible toxicity. CMCS-20H nanoparticles are more resistant to intestinal degradation than unloaded gcIFN-20H by indirect immunofluorescence assay. Then, oral administration were carried out for 42 days. Complement C3 content, lysozyme and total superoxide dismutase activities are highest in CMCS-20H group by serum biochemistry index assays. After challenge with Aeromonas hydrophila, the survival rate in CMCS-20H group is highest (46%), which is 64% higher than the control group (28%). Meanwhile, the tissue bacterial loads (Intestine, spleen, head kidney, trunk kidney, hepatopancreas, muscle and blood) in CMCS-20H group are significantly lower than other groups. By PAS staining analysis, the number of intestinal villi goblet cells and the thickness of mucin in CMCS-20H group obviously increased. CMCS-20H effectively enhances mRNA expressions of some important immune genes (IL-1β, IL-6, TNF-α, IL-2, IFN-γ2 and IgM). The minimal tissue lesions (Intestine, spleen, and trunk kidney) were seen in CMCS-20H group by histopathological examination. 16S rRNA sequencing showed that oral CMCS-20H maintains the intestinal microbiome homeostasis in bacterial infection. The results indicate that the novel nanopeptide CMCS-20H as the immunopotentiator can remarkably boosts fish immunity and precautionary effect by oral administration, address the theoretical mechanisms, and insights into the promising application prospect in aquaculture.